Avaliação estética de variações simuladas da exposição gengival em diferentes tipos faciais : percepção de leigos, ortodontistas e cirurgiões bucomaxilo-faciais - Oliveira, Bruno Gomes de (2017)
The perception of beauty is highly influenced by individual preferences of a rather subjective nature, which makes the objective recognition of a beautiful face a difficult task. The smile is an important element in the overall attractiveness of the human face, and its clinical evaluation is essential for proper diagnosis and treatment planning in dentistry. One particular aspect of smile analysis is the degree of gingival exposure, which must be carefully evaluated to avoid compromising the facial balance in the context of orthodontic or surgical-orthodontic treatment. Thus, assessing the perception of smile aesthetics by laypersons, orthodontists and maxillofacial surgeons through a prospective study could bring relevant information that would aid dental professionals during treatment planning. In this study, a mesofacial, white female model was photographed while displaying a spontaneous smile. The Adobe Photoshop CS6 Extended® software was used to manipulate the original image to simulate three different facial types (mesofacial, brachyfacial and dolichofacial) and to change the degree of gingival exposure to zero, two or four millimeters. Thus, nine different faces were created from the original photograph, with three variations of gingival exposure for each facial type. Three groups of evaluators (laypersons, orthodontists and maxillofacial surgeons) with 50 volunteers each responded to a virtual form created in Google Forms (Mountain View, CA, USA). The digitally manipulated images were scored by the evaluators according to their perceived attractiveness. Kruskal-Wallis and Dunn’s post hoc tests were used to verify the most attractive degree of gingival exposure and the possible influence of the facial type on smile attractiveness. We concluded that laypersons agreed with orthodontists when gingival exposures of 0mm and 2mm were evaluated (p <0.0001), while maxillofacial surgeons chose the 2mm exposure as the most attractive degree of exposure (p <0.0001). Regardless of the facial type, gingival exposures of 0mm and 2mm appear to be preferred by the three groups (p <0.0001).